Model Inkubator Kewirausahaan Hijau: Studi Kasus di Desa Nglanggeran, Kabupaten Gunung Kidul DIY - Suyatna, Hempri; Santosa, Awan; Naryono, Ing Swartanti; Nugroho, Istianto Ary (Jurnal Penelitian Kesejahteraan Sosial, 2018)
This research aims to generate green entrepreneurship incubator models to improve the welfare of rural communities through the utilization of local resources, with the involvement of the greatest community participation and ways to preserve the environment. This research uses of Participatory Action Reserach (PAR), where the research team together with partner organizations in the research sites the process of identification and diagnosis of the problem, developing the model and plans of action, intervention, evaluation and reflection, as well as the return to the initial process with stages that has been developed from the previous.Â The result of Â research found a model of green entrepreneurship incubator based on economic democracy covers three dimensions: the dimension of green entrepreneurs, green institution, and green business. Green entrepreneur dimention requires incubation green knowledge through the implementation of the Green Schools expands the curriculum design, classroom, lab, teachers and cadres green. Green institution dimension requires intervention for the incubation of local wisdom, local organizations, and networks. While the dimensions of green business incubation requires intervention in the management of assets / land, production technology, finance, website (IT), marketing, bookkeeping, and governance of garbage.